Sudden Infant Death Syndrome and the Genetics of Inflammation - Ferrante, Linda; Opdal, Siri Hauge (Frontiers in Immunology, 2015)
Several studies report signs of slight infection prior to death in cases of sudden infant death syndrome (SIDS). Based on this, a hypothesis of an altered immunological homeostasis has been postulated. The cytokines are important cellular mediators that are crucial for infant health by regulating cell activity during the inflammatory process. The pro-inflammatory cytokines favor inflammation; the most important of these are IL-1α, IL-1β, IL-6, IL-8, IL-12, IL-18, TNF-α and IFN-γ. These cytokines are controlled by the anti-inflammatory cytokines. This is accomplished by reducing the pro-inflammatory cytokine production, and thus counteracts their biological effect. The major anti-inflammatory cytokines are interleukin 1 receptor antagonist (IL-1ra), IL-4, IL-10, IL-11, and IL-13. The last decade there has been focus on genetic studies within genes that are important for the immune system, for SIDS with a special interest of the genes encoding the cytokines. This is because the cytokine genes are considered to be the genes most likely to explain the vulnerability to infection, and several studies have investigated these genes in an attempt to uncover associations between SIDS and different genetic variants. So far the genes encoding IL-1, IL-6, IL-10 and TNF-α are the most investigated within SIDS research, and several studies indicates associations between specific variants of these genes and SIDS. Taken together this may indicate that in at least a subset of SIDS predisposing genetic variants of the immune genes are involved. However, the immune system and the cytokine network are complex, and more studies are needed in order to better understand the interplay between different genetic variations and how this may contribute to an unfavorable immunological response.